2013
DOI: 10.1182/blood-2013-05-501569
|View full text |Cite
|
Sign up to set email alerts
|

European LeukemiaNet recommendations for the management of chronic myeloid leukemia: 2013

Abstract: Advances in chronic myeloid leukemia treatment, particularly regarding tyrosine kinase inhibitors, mandate regular updating of concepts and management. A European LeukemiaNet expert panel reviewed prior and new studies to update recommendations made in 2009. We recommend as initial treatment imatinib, nilotinib, or dasatinib. Response is assessed with standardized real quantitative polymerase chain reaction and/or cytogenetics at 3, 6, and 12 months. BCR-ABL1 transcript levels ≤10% at 3 months, <1% at 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
2,099
7
110

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 1,753 publications
(2,295 citation statements)
references
References 165 publications
35
2,099
7
110
Order By: Relevance
“…Whereas approximately one‐third of patients with dose escalation due to BCR‐ABL1 IS > 10% at 3 months achieved MMR, ≈80% of those with dose escalation due to lack of MMR at 12 months or loss of MMR went on to achieve MMR after their dose was escalated. The importance of achieving BCR‐ABL1 IS  ≤ 10% at 3 months is well established (Hanfstein et al , 2012; Marin et al , 2012; Hughes et al , 2014a; Hochhaus et al , 2016b), and this response milestone has been incorporated into CML management guidelines from the European LeukemiaNet and the National Comprehensive Cancer Network (Baccarani et al , 2013; National Comprehensive Cancer Network, 2017); however, optimal management strategies for patients who do not meet this milestone remain unclear. Overall among patients with BCR‐ABL1 IS  > 10% at 3 months (regardless of dose escalation), the rate of MMR by 24 months (36·1%) was comparable to that in the nilotinib 300‐mg twice‐daily arm of ENESTnd (29%) (Hughes et al , 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas approximately one‐third of patients with dose escalation due to BCR‐ABL1 IS > 10% at 3 months achieved MMR, ≈80% of those with dose escalation due to lack of MMR at 12 months or loss of MMR went on to achieve MMR after their dose was escalated. The importance of achieving BCR‐ABL1 IS  ≤ 10% at 3 months is well established (Hanfstein et al , 2012; Marin et al , 2012; Hughes et al , 2014a; Hochhaus et al , 2016b), and this response milestone has been incorporated into CML management guidelines from the European LeukemiaNet and the National Comprehensive Cancer Network (Baccarani et al , 2013; National Comprehensive Cancer Network, 2017); however, optimal management strategies for patients who do not meet this milestone remain unclear. Overall among patients with BCR‐ABL1 IS  > 10% at 3 months (regardless of dose escalation), the rate of MMR by 24 months (36·1%) was comparable to that in the nilotinib 300‐mg twice‐daily arm of ENESTnd (29%) (Hughes et al , 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2013 European LeukemiaNet (ELN) guidelines [12], tyrosine kinase inhibitor (TKI) treatment is recommended lifelong. Despite this indication, several interruption studies showed that it is possible to safely interrupt imatinib treatment without experiencing progression of disease [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these studies, imatinib, nilotinib, and dasatinib are recommended as frontline therapies in patients with newly diagnosed CML-CP in the United States by the National Comprehensive Cancer Network (NCCN) [7] and the European LeukemiaNet (ELN) [11]. These consensus recommendations outline criteria that define optimal response, failure, and warnings for patients treated with TKIs [7,11].…”
mentioning
confidence: 99%
“…These consensus recommendations outline criteria that define optimal response, failure, and warnings for patients treated with TKIs [7,11]. With the approval of the TKI bosutinib-and in certain circumstances ponatinib-for second-and subsequent-line treatment in CML, patients have more treatment options than ever.…”
mentioning
confidence: 99%
See 1 more Smart Citation